Adult interest in using a hypothetical modified risk tobacco product: findings from wave 1 of the Population Assessment of Tobacco and Health Study (2013–14). (6th September 2017) - Pearson, Jennifer L.; Johnson, Amanda L.; Johnson, Sarah E.; Stanton, Cassandra A.; Villanti, Andrea C.; Niaura, Raymond S.; Glasser, Allison M.; Wang, Baoguang; Abrams, David B.; Cummings, K. Michael; Hyland, Andrew
Abstract: Background and aims: The US Family Smoking Prevention and Tobacco Control Act provides a pathway for manufacturers to market a modified risk tobacco product (MRTP). This study examines socio‐demographic and tobacco use correlates of interest in a hypothetical MRTP in a nationally representative sample of US adults. Design: Cross sectional wave 1 data from the 2013–14 Population Assessment of Tobacco and Health (PATH) Study. Setting: Household Audio‐Computer Assisted Self‐Interviews of US adults conducted in 2013–14. Participants: A total of 32 320 civilian, non‐institutionalized adults in the United States. Measurements: Interest in using a hypothetical MRTP ('If a tobacco product made a claim that it was less harmful to health than other tobacco products, how likely would you be to use that product?'), socio‐demographics, tobacco use history and mental health and substance use problems. All estimates were weighted. Findings: Overall, 16.7% [95% confidence interval (CI) = 16.28, 17.18] of US adults reported interest in a hypothetical MRTP. Tobacco use was associated significantly with interest in a hypothetical MRTP, with interest most common among current established smokers (54.4%; 95% CI = 53.31, 55.39) and least common among never tobacco users (3.0%; 95% CI = 2.49, 3.55). Interest in a hypothetical MRTP was associated with experimental e‐cigarette use among current experimental, current established and former smokers. Among non‐smokers, race, age, education and substance use were associated with interest in using a hypothetical MRTP. Conclusions: Among adults in the United States, interest in using a hypothetical modified risk tobacco product is low overall, and highest among current experimental and established smokers. A small percentage of non‐smokers are interested in using a hypothetical hypothetical modified risk tobacco product.